Nuisance parameters, composite likelihoods and a panel of GARCH models. - Pakel, C; Shephard, N; Sheppard, K (Academia Sinica, 2011)
We investigate the properties of the composite likelihood (CL) method for (T × NT ) GARCH panels. The defining feature of a GARCH panel with timeseries length T is that, while nuisance parameters are allowed to vary across NT series, other parameters of interest are assumed to be common. CL pools information across the panel instead of using information available in a single series only. Simulations and empirical analysis illustrate that when T is reasonably large CL performs well. However, due to the presence of nuisance parameters, CL is subject to the "incidental parameter" problem for small T.